“Real life use” of troponin in the emergency department: a survey of over 3000 cases - Vidali, Matteo; Verzotti, Enrica; Cabraz, Nicole; Santi, Francesca; Puma, Alessia; Bellomo, Giorgio; Lupi, Alessandro; Lippi, Giuseppe; Avanzi, Gian Carlo (Biochemia Medica, 2015)
The aim of this study was to identify clinical variables which may be independently associated with positivity of a cardiac troponin I (cTnI) assay in a large population of patients admitted to the emergency department (ED). 3166 subjects, with at least two troponin I tests ordered within 6 hours in the ED, were studied. Patient data were statistically analyzed to identify clinical associations with increased values of Troponin I. Although patients with diagnosis of acute coronary syndrome displayed troponin I values significantly higher than those of other groups, positivity to troponin I (>40 ng/L) was also observed in patients with other clinical conditions. In multivariate analysis, age, elevated heart rate and electrocardiographic changes were independently associated with troponin I positivity at admission. In the whole study population troponin I positivity exhibited high sensitivity and negative predictive value, counterbalanced by low specificity and limited positive predictive value. Troponin I positivity should be combined with history and clinical evaluation and cautiously interpreted in the ED, especially in patients exhibiting factors associated with higher troponin I levels such as older age, elevated heart rate or ECG changes.